What determines top income shares? Evidence from the twentieth century - Jesper Roine; Jonas Vlachos; Daniel Waldenström (Stockholm School of Economics, The Economic Research Institute (EFI), 2007)
This paper examines the long-run determinants of the evolution of top in-come shares. Using a newly assembled panel of 16 developed countries over the entire twentieth century, we find that financial development dis-proportionately boosts top incomes. This effect appears to be particularly strong during the early stages of a country's development. Economic growth is strongly pro-rich which is inconsistent with globalized labor markets determining the incomes of elites. Furthermore, international trade is not associated with increases in top incomes on average, but is so in An-glo-Saxon countries. Finally, tax progressivity has a significant negative ef-fect on top income shares whereas government spending has no such clear impact on inequality.
Keywords: D31; F10; G10; N30; 330; Top incomes; income inequality; financial development; trade openness; government spending; economic development; Einkommensverteilung; Finanzmarkt; Außenhandelsliberalisierung; Entwicklung; Wirtschaftsgeschichte; Industriestaaten